IMPROVING STUDENTS’ INTEREST BY USING PICTURE MEDIA AT TK NUR ASSALAM - Ristyani, Nada Anis; Nurhayati, Nurhayati Nurhayati (IKIP Siliwangi, 2020)
The purpose of this study is to improve students' interest in English vocabulary through picture media in TK Nur Assalam. This research is a Classroom Action Research (CAR). The participants of this research were 6 students. The results obtained from efforts to the improving students interest in English vocabulary using the picture media involving active learners in the learning process. The role of picture media in learning activities is very important for children, especially in the next education level. Teaching and learning activities in early childhood will quickly develop if parents and teachers intensive to develop it. There are several attempts to create a sense of pleasure in early childhood by using picture media in the learning process. From the result of research indicate that when pre-action take result (15%). In cycle I, it increased to (55%) sufficient criteria. In cycle II, it increased again to (85%) good criteria. So, the increase that occurred from the pre-action to the cycle I that is (40%). The increase from cycle I to cycle II that is (30%). And increase from pre-action to cycle II that is (70%). From the research results obtained, then to the improving students interest in English vocabulary can be improved by using picture media in the learning process.Keywords : Students’ Interest, Vocabulary and Picture Media